Hand Grip Strength in Individuals with and without Diabetes - Neha Mukkamala; Jitendra Lakhani; Lata Parmar (Research Highlights in Disease and Health Research Vol. 9, 2023)
Background: Hand grip strength is a simple, non-invasive and low-cost measure of muscle strength and quality. An association between handgrip strength and the prevalence of T2DM could provide a lead for preventive interventions. The present study aimed to measure the handgrip strength in subjects with and without diabetes. Methods: This was an observational study in which subjects with and without diabetes were recruited. Those having type 1 diabetes, upper limb pain, trauma/fracture around the hand within the past year, a history of stroke were excluded. Handgrip strength was assessed in both the groups with a JAMAR dynamometer in the sitting position. Results: 280 subjects, 150 having T2DM and 130 without diabetes were recruited for the study. There was a significant difference (p<0.001) between the handgrip strength of both the groups, with the diabetic group (RGS: 16.06 ± 7.26 kg, LGS: 15.74 ± 7.39 kg) showing lower values compared to non-diabetic group (RGS: 20.58 ± 8.04 kg, LGS: 20.15 ± 7.92 kg). There was a significant difference (p<0.05) in HGS of diabetic and non-diabetic males and females. A significant inverse correlation existed (p<0.05) between age of subjects and handgrip strength and duration of diabetes and handgrip strength. Conclusion: Handgrip strength values were found to be lower in subjects with T2DM than in those without diabetes. As the age and duration of diabetes increased, the handgrip strength decreased.